Compulsory citizenship behavior and employees' contextual performance: Roles of perceived psychological safety and political skill - Hung, Tsang-Kai; Lee, Shu-Chuan; Wu, Yung-Shun; Hsieh, Hui-Min (Social behavior and personality, 2022)
We explored whether compulsory citizenship behavior (CCB) influenced employees' contextual performance via their perception of psychological safety, and examined whether political skill moderated this path. Participants were dyads formed by 139 supervisors and 534 subordinates from businesses in Taiwan. The results reveal that CCB was negatively associated with contextual performance through the mediator of perceived psychological safety. However, there was no significant moderating effect of political skill. This study fills a gap in the literature on CCB. Our results indicate that managers of organizations should pay attention to CCB and to their employees' mental health when trying to encourage enhanced work performance.